2201 fascinating facts - Louis, David (Greenwich House, 1983)
Contents: These intriguing facts and 2197 more like them are collected here to delight, entertain, educate and astonish trivia buffs, esoterica experts, information addicts and anyone else with a passion for collecting odd bits of knowledge.